1997
DOI: 10.1128/jb.179.8.2761-2765.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequence, and properties of the soluble pyridine nucleotide transhydrogenase of Pseudomonas fluorescens

Abstract: The gene encoding the soluble pyridine nucleotide transhydrogenase (STH) of Pseudomonas fluorescens was cloned and expressed in Escherichia coli. STH is related to the flavoprotein disulfide oxidoreductases but lacks one of the conserved redox-active cysteine residues. The gene is highly similar to an E. coli gene of unknown function.Pyridine nucleotide transhydrogenases catalyze the transfer of reducing equivalents between NAD and NADP pools. A membrane-bound, proton-pumping transhydrogenase, specific for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
33
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 17 publications
7
33
0
Order By: Relevance
“…Other reagents were of analytical or higher grade. MDH, MR, and STH were purified from recombinant E. coli as described previously (5, 7,8). The specific activities of the enzyme preparations employed were 11 U of MDH per mg, 6 U of MR per mg, and 276 U of STH per mg.…”
Section: Chemicals and Other Materials Nadh Nadph Nadmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reagents were of analytical or higher grade. MDH, MR, and STH were purified from recombinant E. coli as described previously (5, 7,8). The specific activities of the enzyme preparations employed were 11 U of MDH per mg, 6 U of MR per mg, and 276 U of STH per mg.…”
Section: Chemicals and Other Materials Nadh Nadph Nadmentioning
confidence: 99%
“…Here we address the problems of cofactor depletion in the biological production of hydromorphone by using the soluble pyridine nucleotide transhydrogenase (STH) of Pseudomonas fluorescens (7), an enzyme which can catalyze the transfer of reducing equivalents according to the following equation:…”
mentioning
confidence: 99%
“…Genomic DNA of A. vinelandii ATCC 478 was isolated according to Ausubel et al [6]. The 1.6-kb SacII/XhoI fragment of pSTH1 [3], harbouring the sth gene of P. £uorescens, was labelled using the ECL random prime system according to the manufacturer's protocol (Amersham). DNA was blotted onto Hybond-N+ membrane, detection was achieved with the ECL detection reagents and exposure was to Hyper¢lm-ECL (Amersham).…”
Section: Cloning Sequencing and Sequence Analysismentioning
confidence: 99%
“…Cloning and sequencing of the soluble transhydrogenase gene of P. £uorescens revealed that the enzyme is related to the well-known family of £avoprotein disul¢de oxidoreductases [3]. Members of this family, such as lipoamide dehydrogenase, glutathione reductase and mercuric reductase, are active as homodimers, each monomer consisting of three domains: an N-terminal £avin binding domain, a central nicotinamide cofactor binding domain and a C-terminal domain which is involved in the dimerisation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that lpdC (Rv0462) (10) and gorA (Rv2855) (11) code for LipDH and mycothione reductase, respectively. The sth (Rv2713) gene product bears high sequence identity (ϳ42%) with several well characterized STHs (12)(13)(14). The lpdA (Rv3303c) and lpdB (Rv0794c) genes were annotated as probable LipDHs based on sequence homology to LipDHs from other organisms (15).…”
mentioning
confidence: 99%